Halal Food Crime in Malaysia: An Analysis On Illegal Meat Cartel Issues - ARIFFIN, MOHD FARHAN MD; RIZA, NURUL SYAHADAH MOHD; HAMID, MOHAMMAD FAHMI ABDUL; AWAE, FAREED; NASIR, BADLIHISHAM MOHD (The journal of contemporary issues in business and government, 2021)
Malaysia is a known for its high level of sensitivity in the halal and haram aspects. Its status as an international halal hub reflects the sustainable halal ecosystem in the country, supported by the sensitivities of the government, industry and consumers. Unfortunately, there are irresponsible parties who make halal food a medium of crime. Thus, various food crime issues rise such as food crime, food fraud, food adulteration, food terrorism and cases that cover it. Accordingly, the objective of this article is to target the analysis of food crime issues in Malaysia, focusing on the issue of illegal meat cartels. In addition, various causative factors have been put forward, as well as modern technological alternatives as practical solutions. Data were analysed in a qualitative approach, in which data were collected through document analysis from various primary and secondary sources. As a result, the issue of illegal cartel meat has betrayed all consumers in Malaysia. The government needs to empower halal control in the country, including making practical use of the Industrial Revolution 4.0 era technology.